Intraprostatic Chronic Inflammation is Associated with a Reduced Risk of Prostate Cancer in Patients Elected to a First Random Biopsy Set. Issue 5 (September 2017) - Porcaro, Antonio B.; Novella, Giovanni; de Luyk, Nicolò; Corsi, Paolo; Cacciamani, Giovanni; Sebben, Marco; Tafuri, Alessandro; Processali, Tania; Cerasuolo, Mattia; Cerruto, Maria A.; Brunelli, Matteo; Siracusano, Salvatore; et al.
Objectives: To investigate the associations of clinical factors and intraprostatic chronic inflammatory infiltrate (CII) with the risk of prostate cancer (PCa) in a large contemporary cohort of patients elected to a first random biopsy set. Materials and Methods: The study evaluated 596 patients who were elected to a first random biopsy set because of suspected PCa in the period between September 2010 and September 2015. The multivariate logistic regression model investigated the possible associations of clinical factors and intraprostatic CII with PCa. Results: Prostate cancer was detected in 292 of 596 patients (49%). Intraprostatic CII was detected in 26.3% of cases. Age (odds ratio, OR = 1.060; p<.0001), prostate-specific antigen (PSA; OR = 1.174; p<.0001), prostate volume (PV; OR = 0.951; p<.0001) and abnormal digital rectal examination (DRE; OR = 2.170; p = 0.001) were independent predictors of PCa risk; moreover, intraprostatic CII was an important independent factor lowering the risk of PCa (OR = 0.258; p<.0001) in the multivariate clinical model. Conclusions: In a large contemporary cohort of patients elected to a first random biopsy set, the detection of intraprostatic CII was not negligible (26.3%) and associated with a reduced risk of PCa. In the prostate microenvironment, intraprostatic CII might lower the risk of PCa by activating the response of the immune system at the early stages of cancer induction and progression. Specific serum biomarkers and imaging modalities associated with intraprostatic CII are required. Advanced basic science research is warranted to investigate and develop the controversial topic of intraprostatic chronic inflammation in relation to PCa.